Serbian Civilian Capacities for Peace Operations: Untapped Potential - Milošević, Marko (Journal of Regional Security, 2018)
This article examines Serbia’s capacities to participate in civilian peace operations, including the analysis of legislation regulating international cooperation and contribution to peace operations. Furthermore, based on interviews with representatives of various institutions, it also addresses the key practical challenges that these institutions are currently facing in civilian contribution. It examines the roles of relevant stakeholders, the Ministry of Foreign Affairs, the military and thepolice, with potential participants from other branches of government also included in this analysis. The research sample also included local persons working by contract for international organizations in Serbia, in order to examine the capacities they possess. Several challenges and opportunities for further development of existing frameworks were detected therein. Initial interest expressed by various “civil” ministries to contribute to peace operations (Ministry of Foreign Trade, Ministry of Justice) could contribute to building of CIVCAP. Also, existing institutions, such as Office for cooperation with CSOs and Governmental Department of Human Resources Management could be easily turned into rosters of potential candidates for peace operations. The article argues that a huge potential exists in Serbia, however, its adequate use is prevented by the lack of clear foreign policy goals and coherent government policy. In this regard, the article recommends the government to increase the existing training capacities, coordinate the efforts of various stakeholders and establish two potential rosters of experts.